Adhesion failures on hard coatings induced by interface anomalies - Silva, Carlos W. Moura e (2009)
In this work, the lack of adhesion occurred during the up-scaling of the deposition of tribological coatings in a semi-industrial apparatus is interpreted. The adhesion problems were detected for both hard and self-lubricant coatings from W-Ti-N and W:C systems, respectively, when they were deposited in a 4 cathodes TEER® chamber by reactive unbalanced magnetron sputtering. In spite of cleaning the substrates surface by ion bombardment prior to deposition, by establishing a discharge close to the substrate, insufficient adhesion critical load values were measured by scratch-testing. A powerful set of complementary techniques was used to the detailed analysis of the interfaces in order to understand and overcome the adhesion problems: RBS gave some insights on the nature of the problem by detecting composition anomalies in the substrate/coating interface; Auger spectroscopy was used for identifying the underneath chemical composition close to the interface; cross section TEM gave the final evidence of the presence of a contamination layer attributed to malfunctioning of the ion cleaning process, which was the cause of the lack of adhesion